Detection of DNA sequences attributed to bovine meat and milk factors (BMMF/SPHINX) in food-related samples. (May 2022) - Pohl, Sina; Habermann, Diana; Link, Ellen K.; Fux, Robert; Boldt, Christine L.; Franz, Charles M.A.P.; Hölzel, Christina; Klempt, Martin
Abstract: Circular, single-stranded DNAs (cssDNAs), first described as 'Slow Progressive Hidden INfections of variable X' (SPHINX) and later renamed as 'Bovine Meat and Milk Factors' (BMMF), have been hypothesized to induce colon and breast cancer after consumption of bovine-derived food during early childhood. To date, BMMF sequences have only been published from Bovidae or human sources. To critically assess the hypothesis that ingestion of bovine, explicitly taurine food may trigger or cause cancer, it is of major interest to determine whether BMMF-like cssDNAs possibly also occur in non-bovine food samples. This is highly feasible, since cssDNAs have generally been detected in different animal, plant and environmental samples, and to date no species-specific associations are known. This study, therefore, aimed to investigate whether BMMF occur in a wide spectrum of different foods, including white and red meats, seafood, fruits, vegetables, grain and baby food bought from the local market, as well as in directly collected animal samples such as feces and saliva by PCR-based analysis. For amplification of BMMF/SPHINX-like DNA, recently published and newly designed primer combinations were used. Specific amplicons could be detected in all sample groups tested. For confirmation, different primer pairs specific for BMMF/SPHINX-like DNA were also used to amplify, clone and sequence fragments from several of the different non-bovine food samples. The sequencing results confirmed that the fragments were BMMF/SPHINX-like DNA. This is the first detection of BMMF/SPHINX-like DNA in plants, poultry, wild animals and seafood. The presence of BMMF/SPHINX-like DNA in virtually all investigated non-bovine food groups raises questions with regard to the cancer hypothesis, especially that BMMF/SPHINX from taurine food products are etiologically involved in the development of cancer.